AKIBAT HUKUM PEMBATALAN AKTA PERJANJIAN PENGIKATAN JUAL BELI YANG DIBUAT OLEH PEJABAT PEMBUAT AKTA TANAH TERHADAP PROSES SERTIFIKAT HAK TANAH - Dewa Ayu Bella Saraswati (Universitas 17 Agustus 1945 Samarinda, 2019)
AbstractThe binding purchase agreement is a form of law that arises from the growing need in the community. Land trading deed made before a public notary in a conditional agreement to bind parties who have made the agreement in order to implement the main agreement which is the trading deed made before PPAT (Official Empowered to Draw up Land Deeds). In principle, the land trade agreement is the same as the agreement in general which complies with the requirements of the validity of an agreement as stated in Article 1320 of the Indonesian Civil Codes and Article 1338 Paragraph (1) stating that all agreement which are legally made are used as the law for those who made them. The research was judicial normative. The factors causing the cancelled of the land trading deed was the agreement of the parties because the requirements of cancelled by the court of law for the claim of one of the parties that usually one of the parties did not keep his/her promise and there was an element of an action against the law. The legal consequences of the land trading deed made before a public notary was compensation, cancelled by agreement, and cancelled with compensation. The sue could be done at the court of law (litigation) after the warning was sent to by the injured party to the party that cancelled the agreement or the party who breached the agreement agreed in the land trading deed.